The Dissemination of Science and Science Journalism in Brazilian Universities: Analyzing Strategies that Facilitate Access to Science & Technology - Queiroz, Giuliana Batista Rodrigues de; Becker, Valdecir (Brazilian journalism research, 2016)
This article is a mapping of Brazilian universities that maintain a structured work for Science Journalism and / or the dissemination of science. It analyses the strategies used by the top 50 Brazilian universities for including dissemination of science in their communication activities. In order to do this each institution’s website was examined for the purpose of collecting a large sample size of universities that organize and prioritize the dissemination of science and science journalism, and make their studies and projects available to the public. The dissemination of science is a priority for only 15 universities; ones that have structured science journalism programs. 11 of these universities are among the top 25 in the country which indicates that there is a direct relationship between academic quality and dissemination of science. Thus, this study lends to a deeper understanding of the field of science journalism.